Facts and figures : basic reading practice with answers - Ackert, Patricia; Bernard, Jean.; Navarro, Nicki Giroux de.; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2000)
Animals; How? Why?; Plants; Popular music; Occupations; Interesting People of the World; Exploration and Adventure.
Keywords: English language; Readers; English language -- Textbooks for foreign speakers; Readers